Alterações gástricas em potros submetidos ao estresse do desmame. - Barbara Goloubeff (2006)
This study evaluated 20 160-day-old foals half-bred Brasileiro de Hipismo, raised in Florestal area, state of Minas Gerais, Brazil, born between December 2003 and March 2004. The group was homogeneous, constituted of 12 fillies and 8 colts, 85% of themoriginated from the same stallion. The foals were submitted to abrupt artificial weaning, aiming to produce stress by maternal deprivation, emotional disturbance, uncertainty, and adjustment problems. Based on clinical and endoscopic observation, it was possible to identify two distinct groups: foals that have already had developed gastric changes prior to weaning, and another group that has developed gastritis uponweaning. It was performed an immunologic assessment using a semi quantitative Westernblot to determine concentrations through a double identification of specific antibodies for the ã chain of equine immunoglobulins. The experiment was performed with heterologous antigens (E. coli extract) and equine auto antigens (hepatic extract).The experiment with hepatic extract allowed the differentiation between the IgG reaction profile on the three moments when samples were collected: before, subsequent, and after the weaning, suggesting an extremely clear and significant difference (P= 0,038/Mann Whitney). The absence of reaction to the heterologous antigen panel provides the diagnosis of an autoimmune process, namely the autoimmune gastritis. It was observed a mild anemia in some animals, with severe platelet rise and physiologic leukocytosis caused by stress, with a significant increase of gastrin after weaning. Endoscopies were performed sequentially, two weeks before, 24 hours later, and two weeks after weaning, allowing a clearly verifiable visualization of erosions and gastritis one day after weaning, and followed by bruxism, halitosis and weight-loss. Upon histology, lymphocytic gastritis was discovered, especially at the corpus and margo plicatus areas, being less frequent at the antrum area. Yet, the histochemical coloration revealed intestinal metaplasia, possibly as a residue of phenotypic expression of acidfetal mucines, eventually aggravated by gastritis condition. Positive results to urease activity, even if delayed, suggest the presence of Helicobacter-like microorganisms, precociously colonizing the equine stomach. Emotional factors have an indisputable relationship with the ulcerous stomach episodes, suggesting that the equines have verystrong and distinct emotions engraved in their ethogram. Weaning is a critical period in equines lives, and abrupt weaning is a source of severe anxiety and loss of immunologic homeostasis, evidenced as post-traumatic stress, of permanent duration, causing several physical and behavioral disorders. Gastritis and its complications are clearlycaused by multiple factors, and all efforts must be taken to minimize stress consequences of artificial weaning